IMPLEMENTASI KEBIJAKAN PENGELOLAAN HUTAN PRODUKSI LESTARI DI KALIMANTAN TIMUR - Sarwo Eddi Wibowo; Muhammad Zaini (RJABM (Research Journal of Accounting and Business Management), 2019)
The Natural Production Forest Management (NPFM) policy in East Kalimantan has led to massive deforestation and degradation of East Kalimantan’s natural forests. Until 2012, almost 70% of East Kalimantan,s natural forest production has been damaged, more than that 80% of East Kalimantan,s forestry business has gone bankrupt. While the ecological and social losses are not countless. This is inseparable form the weaknesses in the NPFM policy operating system. In the perspective of administrative science, the effectiveness of NPFM policy implementation is related to the six administrative principles (Max Weber) in NPFM policy. The six neglected administrative principles are : 1) The principle of specialization of organizational functions, resulting in overlapping organizational functions Bureaucracy,  Corporations and Operations in NPFM operation; 2) the formal hierarchical structure principle, as result there is no NPFM tiered supervision system; 3) Priciple of formal rules and standard operating prosedures (SOP), as a result, the NPFM deviation since the process of licensing, implementation and distribution of results; 4) Impersonal relationships, as a result bureaucratic decisions tend not to be objective; 5) The principle of special competence (professional), consequently the NPFM operation results are not optimal; 6) The principle of employing is in accordance with competence, consequently the NPFM performance is poor.